2008
DOI: 10.1007/s10557-008-6110-2
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Mesenchymal Stem Cells by Granulocyte Colony-stimulating Factor in Rats with Acute Myocardial Infarction

Abstract: G-CSF enhanced the migration of systemically delivered MSCs from bone marrow to infarcted heart. However, the beneficial effect of this kind of migration is limited, as cardiac function did not improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 39 publications
4
19
1
Order By: Relevance
“…Mesenchymal stem cells are undifferentiated pluripotential cells present in bone marrow, capable of differentiating into many cell types (chondrogenic, adipogenic, or osteogenic lineages) and may be a suitable autogenous cell source for tissue regeneration. Together with cells coming from the blood, the MSCs are the cells responsible for the first contact with the surface of titanium implants [39][40][41] . The adhesion of these cells to a biomaterial surface can be a major factor mediating its biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells are undifferentiated pluripotential cells present in bone marrow, capable of differentiating into many cell types (chondrogenic, adipogenic, or osteogenic lineages) and may be a suitable autogenous cell source for tissue regeneration. Together with cells coming from the blood, the MSCs are the cells responsible for the first contact with the surface of titanium implants [39][40][41] . The adhesion of these cells to a biomaterial surface can be a major factor mediating its biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…The heart weight in CHF rats increased, but MSCs did not affect this outcome. Nevertheless, despite their effect on morphological structure of the heart, MSCs did not improve the cardiac function, which still remained depressed in CHF rats treated with MSCs; this finding is consistent with other studies [28][29][30].…”
Section: Discussionsupporting
confidence: 92%
“…Our previous results showed that increased surface CXCR4 expression was associated with enhanced MSC migration (Cheng et al, 2008a(Cheng et al, , 2008c. To determine whether SDF-1 enhanced MSC migration through modulation of cell surface CXCR4 expression, MSCs were incubated with SDF-1 before hypoxia/re-oxygenation for 16 h. Flow cytometry analysis showed that SDF-1 tended to increase surface CXCR4 expression compared to non-treated cells, but this did not reach statistical significance ( SDF-1 promotes the secretion of bFGF and VEGF through the SDF-1/CXCR4 axis Paracrine secretion of basic fibroblast growth factors (bFGF) and vascular endothelial growth factor (VEGF) is crucial for protecting MSCs in ischemic tissues (Kinnaird et al, 2004a).…”
Section: Effects Of Sdf-1 Pretreatment On Msc Surface Cxcr4 Expressionmentioning
confidence: 95%
“…Surface CXCR4 expression was analyzed as previously described (Cheng et al, 2008a). Briefly, cells were stained with rabbit anti-CXCR4 antibody (Thermo Fisher Scientific, Fremont, CA, USA) followed by Alexa Fluor 594 goat anti-rabbit IgG (Molecular Probes, Eugene, OR, USA).…”
Section: Flow Cytometry Analysis Of Surface Cxcr4 Expressionmentioning
confidence: 99%
See 1 more Smart Citation